Effects of Tele-nursing in COPD Patients’ Care after Discharge from the Hospital - รู้ธรรม, สุพิน; Kaewprasert, Supaporn (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
This study is a quasi-experimental two-group study with pre-test and post-test. It aimed to investigate the effects of telenursing on the care of patients with chronic obstructive pulmonary disease (COPD) after hospital discharge. between intervention and control groups. The sample group was made up of COPD patients who were admitted to Mae ai hospital. The participants were selected by purposive sampling with 30 subjects to divide the sample into an experimental group of 15 and a control group of 15 subjects for 4th week. The data were analyzed using percentages, standard deviations, means, and independence samples t-tests. The results showed a statistically significant difference in the mean score of knowledge and the mean score of practice between the experimental and control groups (p < 0.00, < 0.00), respectively. The mean score of the COPD assessment test (CAT) and readmission rate within 28 days after discharge was no statistically significant difference between the experimental and the control groups. However, the mean score of CAT in the experimental group decreased more than in the control group, and the readmission rate within 28 days after discharge in the experimental group was less than in the control group during the study period. Tele-nursing could increase the potential for COPD patient self-care after discharge and readmission rate prevention, and telehealth can be used as an alternative for caring for COPD patients after discharge. Keywords: Tele-nursing, Chronic Obstructive Pulmonary Disease, Readmission rate within 28 days